Impact of chronic kidney disease on in‐hospital outcomes and readmission rate after edge‐to‐edge transcatheter mitral valve repair. Issue 4 (15th August 2020) - Sawalha, Khalid; Al‐Akchar, Mohammad; Ibrahim, Abdisamad; Buhnerkempe, Michael; Koester, Cameron; Salih, Mohsin; Bhattarai, Mukul; Tandan, Nitin; Bhatt, Deepak L.; Hafiz, Abdul Moiz
Abstract: Background: Transcatheter mitral valve repair (TMVR) is a treatment option for patients with 3+ or greater mitral regurgitation who cannot undergo mitral valve surgery. Outcomes in patients with chronic kidney disease (CKD) and end stage renal disease (ESRD) are unclear. We sought to evaluate the TMVR in‐hospital outcomes, readmission rates and its impact on kidney function. Methods: Data from 2016 National Readmission Database was used to obtain all patients who underwent TMVR. Patients were classified by their CKD status: no CKD, CKD, or ESRD. The primary outcomes were: in‐hospital mortality, 30‐ and 90‐day readmission rate, and change in CKD status on readmission. Multivariable logistic regression analysis was used to assess in‐hospital, readmission outcomes and kidney function stage. Results: A total of 4, 645 patients were assessed (mean age 78.5 ± 10.3 years). In‐hospital mortality was higher in patients with CKD (4.0%, odds ratio [OR]:2.01 [95% CI, confidence interval: 1.27–3.18]) and ESRD (6.6%, OR: 6.38 [95% CI: 1.49–27.36]) compared with non‐CKD (2.4%). 30‐day readmission rate was higher in ESRD versus non‐CKD patients (17.8% vs. 10.4%, OR: 2.24 [95% CI: 1.30–3.87]) as was 90‐day readmission (41.2% vs. 21% OR: 2.51 [95% CI:1.70–3.72]). Kidney function improved in 25% of patients with CKD stage 3 and in 50% with CKD stage 4–5 at 30‐and 90‐day readmission. Incidence of AKI, major bleeding, and respiratory failure were higher in CKD group. Conclusions: Patients with CKD and ESRD have worse outcomes and higher readmission rate after TMVR. In patients who were readmitted after TMVR, renal function improved in some patients, suggesting that TMVR could potentially improve CKD stage. Abstract : What is known? Patients with CKD or ESRD have worse outcomes after surgical mitral valve replacement. Previous studies showed that outcomes are worse after TMVR in patients with CKD however, ESRD patients were either excluded or under‐represented in most of the studies. Furthermore, the data are limited on the readmission rate and effect of TMVR on kidney function in CKD patients. What is new? Patients with CKD or ESRD had higher in hospital mortality and higher incidence of in‐hospital complications after TMVR. The readmission rate was higher in CKD and ESRD patients. Also, TMVR was associated with improvements in renal function and could potentially improve CKD stage. What is next? Further studies are needed to better understand the outcomes of TMVR on ESRD. Also, the next studies should identify the outcomes of TMVR on all patients including ones who are not readmitted.